The Business Law in Contemporary Times: A Comparison of Indonesia, Vietnam, and Ghana - Kurniawan, I Gede Agus; Disantara, Fradhana Putra; Thuong , Mac Thi Hoai; Nutakor, Briggs Samuel Mawunyo (Faculty of Law, Universitas Muslim Indonesia, Indonesia, 2024)
This study examines the intersection of justice within the framework of business law by analyzing its effectiveness and implementation in Indonesia, Vietnam, and Ghana three nations navigating the challenges of globalization. Justice is conceptualized through the lens of fairness, efficiency, and inclusivity in legal frameworks. By adopting a comparative normative legal research method, this study identifies the critical factors influencing business law implementation: regulatory quality, institutional capacity, political stability, and technological infrastructure. Findings reveal disparities in achieving justice due to corruption, bureaucratic inefficiencies, and weak enforcement mechanisms. While Indonesia grapples with regulatory overlap and decentralized governance challenges, Vietnam demonstrates progressive reforms but struggles with legal clarity. Ghana, despite leveraging political stability, faces significant limitations in infrastructure and enforcement. The study highlights the need for enhanced legal certainty, equitable stakeholder protections, and institutional reforms to align domestic business laws with global standards. Addressing these disparities can foster a more just and competitive business environment, ensuring fair treatment for all economic actors.